OBSERVATIONS OF PECULIAR A STARS - MUNCH, LUIS (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1955)
We determine spectral characteristics of 3 peculiar A stars identified in our previous surveys (HD 50169, HD 51106 and BD+46 1913). We try to establish variability and radial velocity of the objects.
BOL OBS TONAN TACUB
Keywords: OBSERVATIONS, PECULIAR, STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS